1999
DOI: 10.1128/aem.65.5.2015-2019.1999
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Nitrogen Fixation in a Rhizobium etli ntrC Mutant That Overproduces the Bradyrhizobium japonicum Symbiotic Terminal Oxidase cbb 3

Abstract: The ntrC gene codes for a transcriptional activator protein that modulates gene expression in response to nitrogen. The cytochrome production pattern of a Rhizobium etli ntrCmutant (CFN2012) was studied. CO difference spectral analysis of membranes showed that CFN2012 produced a terminal oxidase similar to the symbiotic terminal oxidase of bacteroids in free-living cells under aerobic conditions, with a characteristic trough at 553 nm. CFN2012 produced two c-type cytochromes with molecular masses of 27 and 32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 26 publications
(37 reference statements)
1
2
0
Order By: Relevance
“…To identify NorC protein, we also included in these experiments the R. etli norC mutant. As shown in Figure 5, a 32- and 27-kDa c -type cytochromes, identified previously as the FixP and FixO subunits of the terminal oxygen high-affinity cbb 3 -type cytochrome oxidase (Soberon et al, 1999) were observed in all strains. A third band of about 17 kDa which was observed in WT cells grown with NO 3 − could not be detected in membranes from the norC mutant cultured under the same conditions (Figure 5, lanes 2 and 3).…”
Section: Resultssupporting
confidence: 60%
“…To identify NorC protein, we also included in these experiments the R. etli norC mutant. As shown in Figure 5, a 32- and 27-kDa c -type cytochromes, identified previously as the FixP and FixO subunits of the terminal oxygen high-affinity cbb 3 -type cytochrome oxidase (Soberon et al, 1999) were observed in all strains. A third band of about 17 kDa which was observed in WT cells grown with NO 3 − could not be detected in membranes from the norC mutant cultured under the same conditions (Figure 5, lanes 2 and 3).…”
Section: Resultssupporting
confidence: 60%
“…has been isolated in biofilm in dental waterline tubing [ 40 ], but not found to be related to any human diseases. These are symbiotic nitrogen fixers that can be found in the roots of plants [ 41 ] and they were identified with a similarity of 96–98%. The betaproteobacterial Delftia tsuruhatensis (96% similarity) is a terephthalate-assimilating bacterium [ 42 ] and Diaphorobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…The inoculation of P. vulgaris plants with a R. etli strain having enhanced expression of cbb3 oxidase in bacteroids reduced the sensitivity of P. vulgaris-R. etli symbiosis to drought [113]. Others studies have also reported that genetically modified rhizobial strains overproducing cbb3 oxidase are more efficient in nitrogen fixation under optimal conditions compared to their parental strains [114],[115].…”
Section: Rhizobia Improvement Using Stress Response Genesmentioning
confidence: 99%